2021
DOI: 10.2217/epi-2021-0155
|View full text |Cite
|
Sign up to set email alerts
|

MiRNA-148b and Its Role in Various Cancers

Abstract: miRNA-148b belongs to the family miR-148/-152, with significant differences in nonseed sequences, which can target diverse mRNA molecules. Reportedly, it may undergo deregulation in lung and ovarian cancers and downregulation in gastric, pancreatic and colon cancers. However, there is a need for further studies to better characterize its mechanism of action and in different types of cancer. In this review, we focus on the aberrant expression of miR-148b in different cancer types and highlight its main target g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 149 publications
0
6
0
Order By: Relevance
“… 13 Instead, miR-148b exerts the opposite effect and acts as a tumour suppressor through regulating invasion-, apoptosis- and proliferation-related oncogenes. 14 A case-control study confirmed the NGS ability to detect hotspot mutations in the EBC of lung cancer patients. 15 Another case-control study reported an increase in NSCLC risk associated with overexpression of miR-21 and under expression of miR-486 in plasma and in the exhaled breath condensate (EBC), which would pave the way towards a more extensive use of these biomarkers acquired through a non-invasive method.…”
Section: Introductionmentioning
confidence: 71%
“… 13 Instead, miR-148b exerts the opposite effect and acts as a tumour suppressor through regulating invasion-, apoptosis- and proliferation-related oncogenes. 14 A case-control study confirmed the NGS ability to detect hotspot mutations in the EBC of lung cancer patients. 15 Another case-control study reported an increase in NSCLC risk associated with overexpression of miR-21 and under expression of miR-486 in plasma and in the exhaled breath condensate (EBC), which would pave the way towards a more extensive use of these biomarkers acquired through a non-invasive method.…”
Section: Introductionmentioning
confidence: 71%
“…These observations suggest that CAND1 might mediate invasion and metastasis in ERα-positive breast cancer, possibly through the stabilization of PLK4. In addition, CAND1 might mediate metastasis through the interaction with miR-148b-3p, which has been implicated in mediating the migration of breast cancer cell lines [ 20 , 21 ]; however, the exact mechanism remains to be unidentified.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, targeting CAND1 with miR-148b-3p regulates Schwann cells migration [ 19 ]. miR-148b-3p has also been implicated in mediating the proliferation and migration of breast cancer cell lines [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…binding to mRNAs and thereby promoting degradation of the target mRNA or blocking its translation into protein (19,(68)(69)(70)(71)(72)(73)(74)(75)(76)(77)(78)(79).…”
Section: N2bmentioning
confidence: 99%